2020
DOI: 10.1152/ajpcell.00181.2020
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil heterogeneity and fate in inflamed tissues: implications for the resolution of inflammation

Abstract: Neutrophils are polymorphonuclear leukocytes that play a central role in host defense against infection and tissue injury. They are rapidly recruited to the inflamed site and execute a variety of functions to clear invading pathogens and damaged cells. However, many of their defense mechanisms are capable of inflicting collateral tissue damage. Neutrophil-driven inflammation is a unifying mechanism underlying many common diseases. Efficient removal of neutrophils from inflammatory loci is critical for timely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 310 publications
(439 reference statements)
2
84
0
2
Order By: Relevance
“…Rapid recruitment of neutrophils into infected or injured tissues is critical for the elimination of invading microorganisms and tissue repair (1). Ideally, once the pathogens are cleared, cessation of neutrophil recruitment and removal of emigrated neutrophils from the inflamed site will assure timely resolution of inflammation and return to homeostasis (2)(3)(4). Aberrant neutrophil Abbreviations: AG, azurophilic granule; C5aR, complement 5a receptor; CG, cathepsin G; EC, endothelial cell; JAM-C, junctional adhesion molecule-C; MF, macrophage; MPO, myeloperoxidase; NE, neutrophil elastase; NET, neutrophil extracellular traps; PICD, phagocytosis-induced cell death; PR3, proteinase 3; TEM, transendothelial migration.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid recruitment of neutrophils into infected or injured tissues is critical for the elimination of invading microorganisms and tissue repair (1). Ideally, once the pathogens are cleared, cessation of neutrophil recruitment and removal of emigrated neutrophils from the inflamed site will assure timely resolution of inflammation and return to homeostasis (2)(3)(4). Aberrant neutrophil Abbreviations: AG, azurophilic granule; C5aR, complement 5a receptor; CG, cathepsin G; EC, endothelial cell; JAM-C, junctional adhesion molecule-C; MF, macrophage; MPO, myeloperoxidase; NE, neutrophil elastase; NET, neutrophil extracellular traps; PICD, phagocytosis-induced cell death; PR3, proteinase 3; TEM, transendothelial migration.…”
Section: Introductionmentioning
confidence: 99%
“…Diapedesis of circulating leukocytes is a crucial inflammatory step in immune responses that, when out of control, can cause serious collateral damage (40, 41). To determine whether COVID-19 affects the trafficking potential of circulating leukocytes, we assessed a selection of key trafficking molecules (ICAM-1, ALCAM, CCR2, CD11c) on the different immune cell populations.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, a recent study by Ballesteros et al(6) shows that neutrophil half-life in different tissues under steady-state conditions is similar (except in skin) to their half-life in the blood. It has also been suggested that inflammation may extend neutrophils’ lifespan at the inflammatory tissue site(2, 41, 42). Our data show an increase in half-life (and consequently lifespan) of neutrophils at a sterile inflammatory site if the inflammation induces EG-like conditions.…”
Section: Discussionmentioning
confidence: 99%